Dietary Forsythia suspensa extracts supplementation improves antioxidant status, anti-inflammatory functions, meat fatty acid deposition, and intestinal microbial community in finishing pigs - Liu, Sujie; Wang, Qianqian; Ma, Jiayu; Wang, Jian; Wang, Hongliang; Liu, Li; Long, Shenfei; Piao, Xiangshu (Frontiers in Veterinary Science, 2022)
This study aimed to determine the effects of Forsythia suspensa extracts (FSE) on performance, antioxidant status, inflammatory cytokines, meat quality, meat fatty acid composition, and gut microbial community in finishing pigs. 64 pigs [Duroc × (Landrace × Yorkshire)] with an average initial body weight of 88.68 kg were randomly allotted into two dietary treatments, with 8 replicate pens per treatment (4 pens were barrows, 4 pens were gilts), 4 pigs per pen. The dietary treatments included a corn-soybean meal basal diet (CON) and a FS diet (basal diet 100 mg/kg FSE; FS). Compared with CON, pigs fed FSE showed enhanced (P < 0.05) superoxide dismutase, and glutathione peroxidase contents, and saturated fatty acid (SFA) / polyunsaturated fatty acid (PUFA) ratio, and reduced (P < 0.05) lightness and n-6/n-3 PUFA ratio, as well as tended to increase C20:5n3 content in longissimus dorsi muscle. Moreover, pigs fed FSE showed decreased (P < 0.05) serum cortisol and tumor nuclear factor-α contents, and increased (P < 0.05) serum high-density lipoprotein cholesterol, superoxide dismutase, and glutathione peroxidase contents compared with CON. These pigs also tended to have increased serum total protein and immunoglobulin G contents, and decreased serum low-density lipoprotein cholesterol and interleukin-1β contents compared with CON. In colon, pigs fed FSE had higher (P < 0.05) relative abundance of Bifidobacteriales at order level, Lactobacillaceae and Bifidobacteriaceae at family level, as well as Lactobacillus and Bifidobacterium at genus level compared with CON. In conclusion, dietary Forsythia suspensa extract supplementation effectively improved antioxidant status and anti-inflammatory functions, as well as modulated meat antioxidant capacity, fatty acid composition and gut microbial community in finishing pigs.